MBKM Membangun Desa untuk Peningkatan Mutu Pendidikan Desa Sidodadi Kecamatan Ngantang Kabupaten Malang Jawa Timur - Faizin, Nur; Dwilestari, Kharisma Novita; Arifin , Natasya Berliana (Proceedings of Annual Conference on Community Engagement, 2022)
Merdeka Belajar Kampus Merdeka (MBKM) Building Village this time is focused on the development of the education sector. This is because of the awareness that not only the government has the responsibility to improve the quality of education in Indonesia, but also educators through formal education and other social activists through non-formal education. The method of devotion used in this service is the Asset Based Community-driven Development (ABCD) method. Formal education is carried out by increasing the teacher’s understanding of the creation of creative learning media to improve students’ understanding. Non-formal education is more relaxed and attractive by introducing something new or what they don’t understand with interesting things so that learning is more fun by playing games as a distraction and also as an insert into learning. Students are not only required to memorize but also have to understand and be interested, because by being interested students automatically find out what they don’t know. As for non-formal education, the service is carried out through tutoring activities, drug danger tales, and Ramadan competitions.